2014
DOI: 10.1016/j.econlet.2014.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Is soccer good for you? The motivational impact of big sporting events on the unemployed

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
(8 reference statements)
0
12
0
Order By: Relevance
“…However, the assumed feelgood effect of national athletic success finds little support in a recent analysis based on data from the International Social Survey Programme (ISSP), were sporting success was not directly linked to well-being (Pawlowski et al 2014). Likewise, Doerrenberg and Siegloch (2014), using data of unemployed people from several waves of the German Socio-Economic Panel (SOEP), did not find support for the notion that football tournaments positively impact life satisfaction. Instead, they even find a rather strong negative effect of such tournaments in the case of unemployed men.…”
Section: Hosting Major Sporting Events and Well-beingmentioning
confidence: 89%
“…However, the assumed feelgood effect of national athletic success finds little support in a recent analysis based on data from the International Social Survey Programme (ISSP), were sporting success was not directly linked to well-being (Pawlowski et al 2014). Likewise, Doerrenberg and Siegloch (2014), using data of unemployed people from several waves of the German Socio-Economic Panel (SOEP), did not find support for the notion that football tournaments positively impact life satisfaction. Instead, they even find a rather strong negative effect of such tournaments in the case of unemployed men.…”
Section: Hosting Major Sporting Events and Well-beingmentioning
confidence: 89%
“…Even though we performed robustness checks, the individual heterogeneity present due to the repeated cross-sectional nature of the dataset inevitably leads to a danger of biased coefficients. Therefore, following Doerrenberg & Siegloch (2014), we switched all the game results by six months backward and checked whether our regressions still carried their significance. 32 In case the results still proved significant, this would suggest that the effect in fact lies in some unobservable factors that were not controlled for in our regression.…”
Section: Placebo Gamesmentioning
confidence: 99%
“…In a recent paper, Doerrenberg & Siegloch (2014) examine whether being interviewed before or after an international soccer tournament has implications on several dependent variables, using a panel of unemployed individuals in Germany.…”
mentioning
confidence: 99%
“…Each of the two perspectives is applicable to the context of spectator sport. As a leisure activity, behavioral engagement in spectator sport may provide people with psychological resources (Hallmann et al, 2013) and the opportunity for personal development (Doerrenberg & Siegloch, 2014). Regarding psychological resources, a qualitative study of fans of an AFL team (Doyle et al, 2016) found that attending the teams' games allowed fans to experience positive emotions and feelings of achievement, and reduce daily stress.…”
Section: Live Spectating and Life Satisfactionmentioning
confidence: 99%